Changes in temperature and precipitation extremes in the arid regions of China during 1960–2016 - Wang, Xuyang; Li, Yuqiang; Yan, Meng; Gong, Xiangwen (Frontiers in Ecology and Evolution, 2022)
Extreme weather events have a greater impact on natural and human systems than average weather. The spatial and temporal variation of 16 temperature and 9 precipitation extremal indices was investigated using daily maximum and minimum surface air temperature and precipitation records from 113 meteorological stations in China's arid regions from 1960 to 2016. The warmth indices (warm spell duration; numbers of warm nights, warm days, tropical nights, and summer days) increased significantly. On the contrary, the cold indices (numbers of frost days, ice days, cool days, and cool nights; cold spell duration) decreased significantly. The number of frost days decreased fastest (-3.61 days/decade), whereas the growing season length increased fastest (3.17 days/decade). The trend was strongest for diurnal temperature range (Z = -7.29, P < 0.001) and minimum night temperature (Z = 7.70, P < 0.001). The cold extreme-temperature events increased with increasing latitude, but the warm extreme-temperature events decreased. The warm temperature events decreased at high elevations, whereas cold temperature events increased and the growing season length decreased at high elevations. Compared with temperature indices, the precipitation indices exhibited much weaker changes and less spatial continuity. Overall, changes in precipitation extremes present wet trends, although most of the changes are insignificant. The regionally averaged total annual precipitation for wet days increased by 4.78 mm per decade, and extreme precipitation events have become more intense and frequent. during the study period. The spatial variability of extreme precipitation in the region was primarily influenced by longitude. Furthermore, the climate experienced a warm-wet abrupt climate change during 1990-2000.